Peer review of teaching (PRoT) in higher education – a practitioner's reflection. Issue 5 (2nd September 2016) - Grainger, Peter; Crimmins, Gail; Burton, Kelley; Oprescu, Florin
Abstract: Peer review of teaching (PRoT) is recommended to both develop and assure the quality of teaching practices in Higher Education. An institutional implementation of a peer review process can be viewed as a genuine desire to improve teaching quality or as an instrument of accountability and performativity. There are many approaches to the peer review of teaching operating. This article documents the impact, advantages and disadvantages of direct participation in three peer review of teaching processes.